A Unique Spontaneous Subcapsular Bilioma: Is it an idiopathic variety? - Ananta Shrestha; Thupten Kelsang Lama (Journal of Nepal Medical Association, 2013)
Spontaneous Subcapsular bilioma is an extrabiliary intrahepatic collection of bile in subcapsular location commonly occurring after biliary trauma or surgery. It rarely occurs in absence of any underlying biliary abnormality. We report a such a case with no known underlying biliary tract abnormality except for a solitary gall stone. We bring into discussion whether this type of bilioma can be labeled as idiopathic spontaneous variety in presence of gall stone.